Efektivitas alat tangkap ikan lemuru di Kabupaten Kotabaru, Kalimantan Selatan - Dulmi’ad Iriana; Alexander M. A. Khan; Rita Rostika; Sriati Simpati; Sunarto S (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. This research was conducted on the east coast of Kotabaru District, South Kalimantan on October to November 2011 using survey methods and literatures review. Primary data obtained by direct observation at research location and performing direct interview with various parties; like fishermen, ship owner, TPI officials and other stakeholders in Kotabaru. The result of direct interview obtained that fishing gear to Tembang Fish (including Lemuru) are lift net and mini purse seine. Based on Standardization Efforts formula the most effective fishing gear for catching Lemuru in Kotabaru District is Purse Seine. Socialization needed to fishers that the recommended tool for catching lemuru in Kotabaru District is the purse seine with fishing fleet size 3 GT – 10 GT.Keywords: fishing gear, lemuru fish, Kotabaru, purse seine